Gaya Bahasa dalam Novel Till It’s Gone Karya Kezia Evi Wiadji terhadap Pembelajaran Sastra - Rita Nilawijaya (Jurnal KIBASP (Kajian Bahasa, Sastra dan Pengajaran), 2018)
The purpose of the research are to analyze language style im Till It's Gone and the relevance of language style toward learning in SMA. Data collection used documentation, meanwhile data analysis used fiction analysis. The steps includes identification, classification, interpretation, and conclusion of the data. The result of the research found 18 simile, 8 hyperbole, 5 personification, 2 metaphor, 2 euphemisms, 2 anaphoric, and 3 sarcasm. It is concluded that Till It's Gone Novel by Kezia Evi Wiadji more dominant used simile and hyperbole in language style. For relevance in learning literature for SMA, This novel can be used as additional material in learning Indonesia languange and literature subject for eleventh grade students about intrinsic and extrinsic elements of novel related to three aspects namely language, psychology and cultural background. In summary, Till It's Gone by Kezia Evi Wiadji used comparative, affrimative and allusive language styles. Keywords: Language style and relevance. literary learning